CREATIVITY AT SCHOOL? CONCLUSIONS FROM POLISH STUDY - Marcin, Jewdokimow (European Scientific Journal, ESJ, 2014)
Referring to the visual study, conducted on non-representative sample of Polish secondary schools, the paper discusses a problem of creativity in the school environment. The study allows to distinguish three types of creativity related to school environment (farmed and triggered by school agenda – most frequent in the set; against school agenda; beside school agenda) which points to the conclusion that one may move from a concept of creativity (singular) to a concept of creativities (plural). Almost a half of pupils claim that their school is a creative place. However, it is worth to think about the type of creativity they refer to, since the dominant number of images taken by pupils present creative activities as related to the school agenda.